Terpendole E and its Derivative Inhibit STLC‐ and GSK‐1‐Resistant Eg5. Issue 7 (19th March 2014) - Tarui, Yuka; Chinen, Takumi; Nagumo, Yoko; Motoyama, Takayuki; Hayashi, Toshiaki; Hirota, Hiroshi; Muroi, Makoto; Ishii, Yasuyuki; Kondo, Hisae; Osada, Hiroyuki; Usui, Takeo
Abstract Terpendole E is first natural product found to inhibit mitotic kinesin Eg5, but its inhibitory mechanism remains to be revealed. Here, we report the effects of terpendole E and 11ketopaspaline (a new natural terpendole E analogue) on the Eg5–microtubule interaction and in several Eg5 mutants. 11‐Ketopaspaline is a shunt product from terpendole E, and it shows potent inhibitory activity against the microtubule‐stimulated ATPase activity of Eg5. Unlike other Eg5 inhibitors, such as S‐trityl‐L‐cysteine (STLC) and GSK‐1, both terpendole E and 11‐ketopaspaline only partially inhibited Eg5–microtubule interaction. Furthermore, terpendole E and 11‐ketopaspaline inhibited several Eg5 mutants that are resistant to STLC (Eg5D130A, Eg5L214A) or GSK‐1 (Eg5I299F, Eg5A356T), but with the same extent of inhibition against wild‐type Eg5. Because Eg5D130A and Eg5L214A show cross‐resistance to most known Eg5 inhibitors, which bind the L5 loop, these results suggest that terpendole E and its analogues have a different binding site and/or inhibitory mechanism to those for L5 loop‐binding type Eg5 inhibitors.